AUDIT INVESTIGASI KERUGIAN KEUANGAN NEGARA DALAM PENYIMPANGAN PENGELOLAAN DANA DESA DI KECAMATAN DUSUN SELATAN KABUPATEN BARITO SELATAN KALIMANTAN TENGAH - Tirtakusuma, Andreas Eno (JURNAL ILMIAH EDUNOMIKA, 2024)
The main use of Village Funds is directed for community development and empowerment projects, including the development of basic services: education, health, infrastructure and basic needs. Its effective management is an integral part of overall village financial management in the Regional Revenue and Expenditure Budget (APBD). Transparency and accountability are very important considering the potential for abuse such as Village Fund corruption cases. In Dusun Selatan District, South Buntok Regency, Central Kalimantan Province, there are 24 villages where part of the Village Fund is set aside and collected as participation in the establishment of Village-Owned Enterprises (BUMDes), with the business name: "BUMDes BERSAMA 24." An investigative audit conducted by the Financial and Development Supervisory Agency (BPKP) concluded that (in the 2018-2020 period) there was State financial losses amounting to IDR 583,553,383.00. The research is intended to examine investigative audit practices and the use of audit results in prosecuting Village Fund corruption cases, especially regarding the irregularities in the "BUMDes Bersama 24" management. It was found that the Investigation Audit was the basis for calculating state financial losses in the Village Fund corruption case, even though the audit was not carried out by the BPK (Financial Audit Agency). Keywords: Village Funds, Village BUMN, Investigative Audit